Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
[tex]The\ vertex\ form\ of\ y=ax^2+bx+c:y=a(x-h)^2+k\\\\where\ h=\frac{-b}{2a}\ and\ k=f(h)=\frac{-(b^2-4ac)}{4a}\\-----------------------------\\\\y=-2x^2-12x-10\\\\a=-2;\ b=-12;\ c=-10\\\\h=\frac{-(-12)}{2(-2)}=\frac{12}{-4}=-3\\\\k=f(-3)=-2(-3)^2-12(-3)-10=-2\cdot9+36-10=-18+26=8\\\\therefore:y=-2(x-(-3))^2+8\to\boxed{y=-2(x+3)^2+8}\leftarrow The\ vertex\ form[/tex]
[tex]y-intercept\to f(0)=-2(0^2)-12(0)-10=\boxed{-10}\leftarrow y-intercept[/tex]
[tex]x-intercept\ if\ y=0\\\\-2x^2-12x-10=0\ \ \ \ \ |divide\ both\ sides\ by\ (-2)\\x^2+6x+5=0\\x^2+x+5x+5=0\\x(x+1)+5(x+1)=0\\(x+1)(x+5)=0\iff x+1=0\ or\ x+5=0\\\\\boxed{x=-1\ or\ x=-5}\leftarrow x-intercept[/tex]
[tex]y-intercept\to f(0)=-2(0^2)-12(0)-10=\boxed{-10}\leftarrow y-intercept[/tex]
[tex]x-intercept\ if\ y=0\\\\-2x^2-12x-10=0\ \ \ \ \ |divide\ both\ sides\ by\ (-2)\\x^2+6x+5=0\\x^2+x+5x+5=0\\x(x+1)+5(x+1)=0\\(x+1)(x+5)=0\iff x+1=0\ or\ x+5=0\\\\\boxed{x=-1\ or\ x=-5}\leftarrow x-intercept[/tex]
y=-2x^2-12x-10
to find the x value of the vertex find the axis of symmetry which is
-b/2a
=12/2(-2)
=-3
to find the y value of the vertex sub the axis of symmetry back into the original equation.
y=-2(-3)^2-12(-3)-10
y=8
vertex=(-3,8)
to put it into vertex form use y=a(x-h)^2 +k where h and k are the x and y values of the vertex respectively.
y=-2(x--3)^2 +8
y=-2(x+3)^2+8
to find the x intercept let y=0
-2x^2-12x-10=0
x^2+6x+5=0
use quad formula and you will get
x=-5 and -1
to find the y intercept let x=0
y= -2(0)^2-12(0)-10
y=-10
to find the x value of the vertex find the axis of symmetry which is
-b/2a
=12/2(-2)
=-3
to find the y value of the vertex sub the axis of symmetry back into the original equation.
y=-2(-3)^2-12(-3)-10
y=8
vertex=(-3,8)
to put it into vertex form use y=a(x-h)^2 +k where h and k are the x and y values of the vertex respectively.
y=-2(x--3)^2 +8
y=-2(x+3)^2+8
to find the x intercept let y=0
-2x^2-12x-10=0
x^2+6x+5=0
use quad formula and you will get
x=-5 and -1
to find the y intercept let x=0
y= -2(0)^2-12(0)-10
y=-10
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.